Pengembangan LKPD Berbasis Model ARCS Pada Pokok Bahasan Kesetimbangan Ion dan pH Larutan Penyangga - Sasya Hanifha; Susilawati; Jimmi Copriady (Journal of Research and Education Chemistry, 2021)
This study aims to develop student worksheets based on the ARCS model on ionic equilibrium and pH of the buffer solution subject, determining the validity of student worksheets of the aspects of content, ARCS characteristics, language, presentation, graphics and find out user responses through student worksheets based on ARCS models on ionic equilibrium and pH buffer solution subject. This research is a Research and Development (R&D) with a 4-D development model. The object of this research is student worksheets based on the ARCS model. The data collection instruments were in the form of validation sheets given to three validators and user questionnaires given to teachers and students. After two revisions, the validity results obtained in the aspects of content, ARCS characteristics, language, presentation and graphics, respectively, namely 93.75%, 93.75%, 98.33%, 97.92% and 98%. the average score was 96.33% that comes to valid criteria. student worksheets which was valid by the validator tested one by one on 3 students who had studied the ion balance and pH of the buffer solution. Furthermore, asking for response to 3 chemistry teachers and 20 students resulted the teacher’s response and resultied a student response 91.07% and 79.73% that comes to very good criteria. Based on the results of the data analysis, it concluded that student worksheets based on the ARCS model was valid and can be used during high school chemistry lessons on the ion balance and pH of buffer solution subject.